The Toronto Concussion Study: a longitudinal analysis of balance deficits following concussion in community-dwelling adults. (23rd August 2020) - Sweeny, Michelle; Inness, Elizabeth L.; Singer, Jonathan; Habib Perez, Olinda; Danells, Cynthia; Chandra, Tharshini; Foster, Evan; Comper, Paul; Bayley, Mark; Mochizuki, George
ABSTRACT: Objective: To characterize recovery of balance deficits in community-dwelling adults with concussion. Hypothesis: Balance measures will improve 2 weeks after injury and persist over 12 weeks. Design: Prospective longitudinal observational study. Methods: Assessments included the Balance Error Scoring System (BESS) and quiet standing during eyes open, eyes closed, and a cognitive dual task. Recovery was determined using a Hierarchical Growth Curve Model (HGCM) at Week1 (n = 61), Week2 (n = 58), Week4 (n = 53), Week8 (n = 51), and Week12 (n = 39) post-injury. Within-individual follow-up analysis was conducted using the coefficient of variation (quiet standing measures) and a reliable change index (BESS) on 28 individuals with concussion assessed at all 5 time points. Results: Self-reported symptom score recovered between Week 4–8. Anteroposterior COP velocity (eyes closed) was the only variable to show statistically significant ( p < .05) recovery in the HGCM. The within-individual analysis identified fewer than 43% (12/28) of participants recovered by Week 12, relative to their own Week 1 assessment. Conclusions: While recovery of balance deficits was observed in 1 variable over 12 weeks, less than half of the participants included in all assessments demonstrated improvement in balance outcomes. Future research and clinical practice should focus on the unique characteristics of community-dwelling adults with concussion to optimize recovery in this cohort.